2020
DOI: 10.3389/fendo.2019.00926
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover Markers and Probable Advanced Nonalcoholic Fatty Liver Disease in Middle-Aged and Elderly Men and Postmenopausal Women With Type 2 Diabetes

Abstract: Objective: Type 2 diabetic patients have a higher incidence of nonalcoholic steatohepatitis (NASH) and advanced stages of fibrosis, and nonalcoholic fatty liver disease (NAFLD) is associated with impaired bone health. We aimed to investigate whether bone turnover is associated with the probable presence of NASH and fibrosis.Methods: In total, 4,937 diabetic participants from Shanghai, China were enrolled in 2018. Subjects with NAFLD were categorized into simple NAFLD and probable NASH groups based on the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, similar studies focusing on T2DM population have been scarce and controversial so far. A study in a cohort of 4937 subjects by Wang et al 22 reported that N-mid fragment of OCN was negatively associated with advanced NAFLD status including nonalcoholic steatohepatitis and significant fibrosis in middle-aged and elderly men and postmenopausal women with T2DM. Nonetheless, another study in postmenopausal women with T2DM and impaired glucose regulation presented a positive correlation of serum OCN levels and NAFLD fibrosis score, a non-invasive test evaluating the severity of hepatic fibrosis caused by NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar studies focusing on T2DM population have been scarce and controversial so far. A study in a cohort of 4937 subjects by Wang et al 22 reported that N-mid fragment of OCN was negatively associated with advanced NAFLD status including nonalcoholic steatohepatitis and significant fibrosis in middle-aged and elderly men and postmenopausal women with T2DM. Nonetheless, another study in postmenopausal women with T2DM and impaired glucose regulation presented a positive correlation of serum OCN levels and NAFLD fibrosis score, a non-invasive test evaluating the severity of hepatic fibrosis caused by NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Additionally, few studies have investigated the correlation between serum OCN levels and MAFLD in T2DM patients, and the findings from different studies are inconsistent. For example, Wang et al 22 reported that serum OCN levels were negatively associated with advanced NAFLD status in middle-aged and elderly men and postmenopausal women with T2DM. However, another study in postmenopausal women with either T2DM or impaired glucose regulation presented a contrary result, in which a positive correlation between OCN levels and NAFLD fibrosis score was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Whether metformin treatment is associated with a reduced risk of fractures remains controversial ( 26 ). Furthermore, metformin was shown to improve liver metabolism during GC excess ( 5 ), which in turn could have positive effects on bone health ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade inflammation mediated by these factors may also influence bone metabolism in obese patients [ 24 ]. Procollagen-1 N-terminal peptide (P1NP), a marker of bone and osteoporosis risk, may also be altered in patients with metabolic syndrome, and also in the inflammatory context of non-alcoholic fatty liver disease (NAFLD) [ 26 , 27 ]. However, little is known of the pathophysiological mechanisms and consequences of P1NP dysregulation in psoriasis.…”
Section: Introductionmentioning
confidence: 99%